Linguoculturological Study of the French Language - Oripova Kamola Davlatovna (Genius Journals, 2023)
This article discusses a comprehensive study of the lexical and grammatical features of the French language, which allows us to describe the originality and originality of the linguoculture we study, reflected at the appropriate levels of the language system, as well as the implementation of linguoculturological teaching of a foreign language to students and a significant change in the organization of the educational process.
Keywords: linguoculturological component; linguistic research; integral phenomenon